ادارہ تحقیقات اسلامی سے متعلقہ دستاویزات: ایک تجزیاتی مطالعہ .................................................................................. The Analytical Study of Documents related to Islamic Research Institute - افراق, طاہرہ (FIKR-O NAZAR فکر ونظر, 2018)
Establishment of Islamic Research Institute was one of the significant initiatives after creation of Pakistan. IRI is one of the Constitutional Institutions which has been established for developing and shaping the ideological basis of Pakistani society in accordance with the objective resolution. The documents about creation, characteristics, objects, purposes and establishment of Institute are not only pertinent to IRI but also valuable in term of history of subcontinent and Pakistan. These documents have been selected for this study due to the irrefutable prominence at historical, constitutional and national levels. The study of these documents is important in perspective of challenges faced by Pakistani society. These documents have been prepared by those personalities who hold phenomenal educational and research background. They have the wisdom and vision of future of Pakistan and its society. The study of these documents manifest sketch of that Pakistan intended by its creators. The documents that are part of this study include objectives resolution, constitutions of Islamic Republic of Pakistan 1956 and 1962. Official orders, ordinances and statutes related to IRI and IIUI are also discussed in this study. Minutes of important meetings related to IRI are also part of this study.